2017
DOI: 10.14687/jhs.v14i4.4825
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 8-week thera-band exercises on male swimmers’ 100 m freestyle swimming performance

Abstract: The aim of this study is to investigate 8 weeks Thera-Band trainings' effects on male swimmers' 100 m freestyle swimming performance.The study group is created by 20 (n = 20) licenced male athletes that had trained at least 3 days in a week and have been active in swimming sport at least 3 years in Gebze Genclerbirligi Swimming Club 20 (n = 20). Athletes were divided into experiment group (n = 10) and control group (n = 10) randomly. Training programme was applied to the study group for 55-60 minutes for 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The authors also noted an improvement in horizontal jump, vertical jump, and push-ups after the prescribed 8-week training block. Similar conclusions were drawn by Gönener et al [ 20 ], who stated that training with the use of Thera-Band tapes (including their use to engage core muscles) improves the performance of swimmers. Core muscle training has been widely researched in the recent years, and even though it seems like there is an universal conviction that the correct strength of stabilizing muscles improves the athletic level of competitors, some papers show only marginal impact of this type of training on the final sporting success [ 7 , 10 , 19 ].…”
Section: Introductionsupporting
confidence: 87%
“…The authors also noted an improvement in horizontal jump, vertical jump, and push-ups after the prescribed 8-week training block. Similar conclusions were drawn by Gönener et al [ 20 ], who stated that training with the use of Thera-Band tapes (including their use to engage core muscles) improves the performance of swimmers. Core muscle training has been widely researched in the recent years, and even though it seems like there is an universal conviction that the correct strength of stabilizing muscles improves the athletic level of competitors, some papers show only marginal impact of this type of training on the final sporting success [ 7 , 10 , 19 ].…”
Section: Introductionsupporting
confidence: 87%
“…However, contradictory results are also seen on their effect on the performance (Cissik, 2011;Patil et al, 2014). In alignment with the performed study, Gönener et al (2017) found out that core exercises have effects on 100 m swimming performance of male swimmers aged 13-15, with back stroke style and they emphasize that core exercises should be used in groundwork exercises. Patil et al (2014) state that, as a result of the study they carried out with 60 young swimmers with a mean age of 14,2±1,49, 6 weeks of core exercises have effect on 50 m free style swimming (p<0,05).…”
Section: Resultssupporting
confidence: 66%
“…Also, Gencer [19] observed that during the experiment, there was a significant improvement in time needed to swim the distance of 50 meters by the experimental group in relation to the control group [19]. Similar conclusions came from Gönener et al [20], who after the tests stated that training with the use of Thera-Band tapes (including engaging core muscles) improves the performance of swimmers [20]. Despite the interest of the authors of numerous publications on the issue of core muscle training and despite the universal recognition that the right strength of stabilizing muscles improves the athletic level of competitors, there are papers that show only the marginal impact of this training on the final sporting success [7,10,19].…”
Section: Introductionmentioning
confidence: 53%